The performance of membrane bioreactor in treating temperature municipal wastewater [electronic resource] - 490328 Abdullah Ali Al Amri; Fakulti Kejuruteraan Awam (2010)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2010